CENA DE INTERIOR II AND QUEERMUSEU: CARTOGRAPHY OF THE DIFFERENCES IN BRAZILIAN ART SILENCED AT PORTO ALEGRE (2017) (Palíndromo, 2019)
This article intende to present the diferente narratives produced about Adriana Varejão ‘s “Cena de Interior II (1994)”, which was part of the exibition “Queermuseu: Cartografias da Diferença na Arte Brasileira” inaugurated and closed in 2017, in space Santander Cultural (Porto Alegre). Using studies on image, history and visual culture, this article analyzes the different narratives that this work provided in some of the exhibitions. Thinking that objects in a state of exposure accumulate discourses from different expository contexts (such as a film narrative), there is a network of (non-neutral) choices that are not exhausted in curatorial discourse. In this way, we can affirm that the same image can suffer different interpretations according to the exhibition space in which it is, as well as from the central theme of the exhibitions in which the work is present. Focusing on the specific study of the narrative produced by the work in the exhibition “Queermuseu”, we evidenced the attacks of the conservative groups, which led to its closure (silencing).
Keywords: cultural history of images; contemporary art; art exposition